Collodion Baby - A. A. Made Berastia Anis Savitri; Ida Ayu Sri Kusuma Dewi (PT Kalbe Farma Tbk., 2022)
Collodion baby (CB) is a rare dermatological condition worldwide of 1: 300.000 birth. A Collodion baby is a newborn whose entire body is covered with an adherent, supple, parchment-like membrane. Collodion baby in a manifestation of various hereditary conditions, including Harlequin orchestras’ (HI), lamelar orchestras’ (LI), non-bullous congenital ichtyosiform erythroderma (NBCIE), trichothiodystrophy metabolic disease, and endocrine disease. We report two collodion babies cases with peeling skin, passive movement, and poor feeding. Both cases were hospitalized in the humidity-controlled incubator. Water and topical treatment were used for daily bathing to prevent infection. Collodion baby merupakan kelainan dermatologi yang sangat jarang; prevalensi di dunia adalah 1:300.000. Istilah ini mengacu pada kondisi bayi baru lahir dengan kulit yang ditutupi membran tipis seperti perkamen. Collodion baby merupakan manifestasi berbagai kondisi yang diturunkan seperti Harlequin ichthyosis (HI), lamelar ichthyosis (LI), non-bullous congenital ichthyosiform erytroderma (NBCIE), trichothiodystrophy metabolic disease, dan endocrine disease. Kami melaporkan dua kasus bayi collodion dengan kulit terkelupas, gerakan pasif, dan kesulitan menyusu. Kedua kasus dirawat di ruang Perinatologi dalam inkubator dengan kelembapan terkontrol dan perawatan topikal untuk mencegah infeksi dan menjaga kulit tetap lembap.